Cultural implications in innovation adoption: an analysis in three countries - Mendes, Isadora; Lazzari, Fernanda; Salvador, Christian Kleiton (Journal of Sustainable Competitive Intelligence, 2023)
Purpose: The study aimed to evaluate the relationship of two national cultural dimensions (individualism and uncertainty avoidance) with the consumer innovativeness. Methodology/approach: A descriptive research as conducted with three groups from three different countries, which evaluated, through a survey, the propensity of the respondents to look for innovations actively and independently. Originality/Relevance: Considering companies are constantly introducing new products and services in countries where cultural traits are different, the understanding of the consumer behavior is fundamental for evaluating the acceptance of these innovations. Key findings: It was observed that groups with strong collectivists characteristics, Brazilians and Colombians, tend to rely on the positive experience of friends and relatives to adopt an innovation. Regarding the uncertainty avoidance dimension, the results showed no significant differences among the three groups. Theoretical/methodological contributions: With the constant intensification of the international trade, it is necessary to make an understanding of the peculiarities of a target audience for products and services, in order to create appropriate positioning strategies, because the levels of individualism of a culture act directly on consumers’ perceptions regarding the adoption of innovation.